An Information System Proposal to Deal with Critical Factors in Entrepreneurship Training Programs - Menolli, André; Coelho, Ricardo GonçAlves; Coelho, João (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Nowadays, entrepreneurial and soft skills are as important as technical knowledge, emerging as an essential prerequisite for up-and-coming professionals. Entrepreneurship programs have become a widely adopted approach for enhancing and developing these essential skills. Problem: In the undergraduate context, many aspects of these programs do not work well. This can be attributed to insufficient program planning or the misconception that undergraduate students possess the capacity to make managerial decisions. Solution: We have proposed an entrepreneurship training program focusing on a preliminary start-up and an Information System to support the early stages of the program, aiming to address critical deficiencies observed in existing programs. IS Theory: We employ Design Science Research as the foundation for shaping both our program and the information system, drawing from insights gleaned from various other programs and existing literature. Method: The research is exploratory, and its assessment involves the program implementation within a university setting. The results were analyzed using a quantitative approach to provide a comprehensive understanding of the outcomes. Summary of Results: The results show that the program supported by the system effectively addresses critical challenges. It facilitates the creation of well-structured teams and guides these teams toward addressing real and relevant problems aligned with their areas of expertise. Contributions and Impact in the IS area: The main contribution is to propose an entrepreneurship program approach and a system to support it in critical phases. It demonstrates how information systems, when applied to specific domains, can prove to be highly beneficial. The proposed system fosters essential initiation aspects, thereby enhancing the overall effectiveness of the program.